Ecotourism in Marine Protected Areas as a tool to valuate natural capital and enhance good marine governance: A review - Casimiro, Daniela; Ventura, Maria Anunciação; Botelho, Andrea Zita; Guerreiro, José (Frontiers in Marine Science, 2023)
Marine Protected Areas (MPAs) are essential to reach the UN Ocean’s Decade challenges and the Sustainable Development Goal 14 (life bellow water – conserve coastal and marine areas), and their crucial role for the health of the planet was highlighted in the United Nations Ocean Conference (UNOC 2022). However, often these MPA’s are no more than Paper Parks, with poor financial and human resources, thus lacking effectiveness. Moreover, they frequently trigger conflicts with local communities, by imposing restrictions to their activities with no alternative or compensations, causing serious governance inefficiencies. Thus, within the UN Oceans Decade, MPA’s must face simultaneously three of the challenges: Protect and restore ecosystems and biodiversity (Challenge 2); Develop a sustainable and equitable ocean economy (Challenge 4) and Change humanity’s relationship with the ocean (Challenge 10). To address those challenges, it becomes clear that management models of MPA’s had to find ways to value natural capital and, at the same time, involve local communities and stakeholders in the governance processes. The conservation of biodiversity has both direct and indirect economic benefits for many sectors of the economy, namely tourism, being ecotourism considered one of the segments particularly adequate to value natural capital. Ecotourism, defined as “environmentally responsible travel and visitation to relatively undisturbed natural areas”, to enjoy and appreciate nature, is often used to enhance the natural capital, while protecting and promoting protected areas. Several studies have been carried out about ecotourism in MPA’s all over the world, particularly in the 21st century. In this article, we analyzed several case studies focusing ecotourism in MPAs, to better understand the connection between the development of this industry, the development of sustainable blue economy, and the efforts for ocean conservation. From the analysis conducted, we conclude that ecotourism development and community participation are of paramount importance in achieving sustainable development in MPAs, although there is still room to new advances improving good marine governance.